Språkmöte och språkhistoria - Sävborg, Daniel; Asu, Eva Liina; Laanemets, Anu (Nordistica Tartuensia, 2020)
The fifteenth volume in the series "Studies in the History of the Swedish Language" consists of 21 articles chosen from the presentations of the 15th conference on Swedish language history that was organized by the Department of Scandinavian studies at the University of Tartu, 13-15 June 2018. The main theme of the book comprises language contact and language history. The contacts between Swedish and other languages and what these involve have constituted an active area of research during the past years. This topic is naturally linked to the historical situation of Swedish in Estonia. The articles in the volume cover a wide spectrum of research areas, including language variation and change, Swedish dialects, historical corpus linguistics, multilingualism, translation theory, onomastics, etc. With this volume the editors hope to further stimulate the notable increase of interest in the history of Swedish and not least in the study of various language contacts.